Offline assistance optimization of a soft exosuit for augmenting ankle power of stroke survivors during walking - Siviy, Christopher (IEEE Robot Autom Lett, 2020)
Locomotor impairments afflict more than 80% of people poststroke. Our group has previously developed a unilateral ankle exosuit aimed at assisting the paretic ankle joint of stroke survivors during walking. While studies to date have shown promising biomechanical and physiological changes, there remains opportunity to better understand how changes in plantarflexion (PF) assistance profiles impact wearer response. In healthy populations, studies explicitly varying augmentation power have been informative about how exosuit users are sensitive to changes in PF assistance; however there are challenges in applying existing methods to a medical population where significantly higher gait variability and limited walking capacity exist. This paper details an offline assistance optimization scheme that uses pre-recorded biomechanics data to generate torque profiles designed to deliver either positive or negative augmentation power in PF while being less sensitive to stride-by-stride variability. Additionally, we describe an admittance-control strategy that can effectively deliver PF force with RMS error less than 10 N. A preliminary study on six people poststroke demonstrates that offline assistance optimization can successfully isolate positive and negative augmentation power. Moreover, we show that in people poststroke, positive augmentation power effected changes in total positive ankle power while delivering negative augmentation power had no effect on total negative ankle power.